PENGARUH KOMUNIKASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT JEMBO CABLE COMPANY KOTA TANGERANG - Sunardi, Didi; Ayuningtiyas, Ira (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
The aim of this research is to determine the influence of work communication and work compensation on employee performance at PT Jembo Cable Company Tbk in Tangerang City. The method used is quantitative. The population and sample consist of 90 respondents. Data analysis uses validity tests, reliability tests, classical assumptions, regression analysis, correlation analysis, determination analysis, and hypothesis testing. The research indicates a strong correlation between communication (0.630) and compensation (0.580) with employee performance. The multiple linear regression equation is Y = 11.321 + 0.418X1 + 0.307X2, meaning that when variable X1 is increased by 1 unit, variable Y increases by 0.418 units at a constant of 11.321, and when variable X2 is increased by 1 unit, variable Y increases by 0.307 units at a constant of 11.321. The coefficient of determination value of 46.8% indicates the contribution of communication and compensation to improving employee performance, while the remaining 46.8% is influenced by other factors. The F hypothesis test yields an F value > F table or (38.308 > 2.710). Thus, H03 is rejected and Ha3 is accepted, meaning there is a significant simultaneous influence of communication and compensation on employee performance. These findings can provide input for policies and practices aimed at improving employee performance at PT Jembo Cable Company Tbk.